Mechanical Engineering and Mechatronics Handbook - Kumar, D (MLI Handbook Series, 2022)
This handbook covers basic concepts in mechanical engineering and mechatronics, including stress and strain, mechanics of solids, internal combustion engines, refrigeration, fluid mechanics, control systems, actuation, robotics, electro-mechanical systems, hydraulics, and more. Using step by step examples and numerous illustrations, the book is designed with a self-teaching methodology, including a variety of exercises with corresponding answers to enhance mastery of the content. Mechanical engineering and mechatronics concepts provide the skill sets in cross-disciplinary subjects which are needed in modern manufacturing industries. Features: Covers basic concepts in mechanical engineering and mechatronics, including stress and strain, mechanics of solids, internal combustion engines, refrigeration, fluid mechanics, control systems, actuation, robotics, and electro-mechanical systems Includes a variety of exercises (with answers), such as conceptual questions, multiple choice, and fill-in the blanks, to enhance mastery of the content